1999
DOI: 10.1159/000008006
|View full text |Cite
|
Sign up to set email alerts
|

Role of Somatosensory Feedback from Tools in Realizing Movements by Patients with Ideomotor Apraxia

Abstract: In order to investigate the underlying mechanism of ideomotor apraxia, we studied 9 patients who could not mime using tools despite the ability to manipulate actual tools normally. In all the mime tasks, visually presented tools or model gestures by examiners were fundamentally ineffectual in improving the patients’ performances. Even the remarkable improvement demonstrated when using actual tools disappeared immediately after the subjects took their hands off them. In a further experiment, 4 of the 9 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…First, the severity of the deficit depends on the task condition and decreases from pantomime to actual use. This dependency of tool-use deficit on task conditions has frequently been reported (Buxbaum et al 2000;Clark et al 1994;De Renzi 1990;Goldenberg and Hagmann 1998;Goldenberg et al 2004;Hermsdörfer et al 2006Hermsdörfer et al , 2011Laimgruber et al 2005;Liepmann 1908;Wada et al 1999;Randerath et al 2011). The finding emphasizes the beneficial role of context and mechanical task constraints for ameliorating an apraxic movement deficit present during pantomime (see Introduction).…”
Section: Effects Of Brain Damagesupporting
confidence: 61%
See 1 more Smart Citation
“…First, the severity of the deficit depends on the task condition and decreases from pantomime to actual use. This dependency of tool-use deficit on task conditions has frequently been reported (Buxbaum et al 2000;Clark et al 1994;De Renzi 1990;Goldenberg and Hagmann 1998;Goldenberg et al 2004;Hermsdörfer et al 2006Hermsdörfer et al , 2011Laimgruber et al 2005;Liepmann 1908;Wada et al 1999;Randerath et al 2011). The finding emphasizes the beneficial role of context and mechanical task constraints for ameliorating an apraxic movement deficit present during pantomime (see Introduction).…”
Section: Effects Of Brain Damagesupporting
confidence: 61%
“…Their errors vary widely from severe errors, such as no movement response or unrecognizable movements, to milder errors, such as incorrect hand grips at the imagined tool. A number of studies reported that patients perform better when they are allowed to actually use tools as compared to when they pantomime tool use (Buxbaum et al 2000;Clark et al 1994;De Renzi 1990;Goldenberg and Hagmann 1998;Goldenberg et al 2004;Hermsdörfer et al 2006;Laimgruber et al 2005;Liepmann 1908;Wada et al 1999), although errors or even inability of actual tool use have also been reported (De Renzi and Luchelli 1988;Goldenberg and Hagmann 1998;Goldenberg and Spatt 2009;Westwood et al 2001;Randerath et al 2011). In one of these studies (Goldenberg et al 2004), a neutral wooden implement resembling the handle of the tools was provided instead of the real tool (i.e., a 10-cm-long stick with a diameter of 3 cm instead of the hammer).…”
Section: Introductionmentioning
confidence: 99%
“…In light of IMA patients' ability to respond to object structure, as exemplified by clinical studies demonstrating patients' improved performance when allowed to manipulate real objects (Clark et al, 1994;Goldenberg et al, 2004;Hermsdorfer et al, 2006;Wada et al, 1999), we speculated that adding affordance cues might result in better objectrelated learning of hand posture. We created a stimulus set of novel gestures and novel tools, paired in such a way as to reflect highly afforded and low-afforded action-tool relationships.…”
Section: Role Of Structural Object Information In New Learningmentioning
confidence: 99%
“…There is some evidence that teaching people with dyspraxia to use cognitive strategies to manage tasks improves their performance on both trained and un-trained tasks, and that those improvements endure [32]. To enable participation in any of these interventions, techniques such as sensory and proprioceptive stimulation of the limbs, verbal or physical cueing, and facilitating normal movement patterns may be used [11,33].…”
Section: Introductionmentioning
confidence: 99%